PHOTOCATALYTIC REMOVAL OF TOXIC TEXTILE DYES FROM WATER USING CU-DOPED ZNO NANOPARTICLES UNDER NATURAL SUNLIGHT - D., Sonia; Vasam, E.K. Kirupa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
An efficient copper-doped ZnO (Cu-doped ZnO) nanoparticle was synthesized in nano form via co-precipitation using zinc sulfate heptahydrate as a precursor. The synthesized Cu-doped ZnO nanoparticle was characterized using X-ray diffraction (XRD), FT-IR, UV-DRS, SEM with EDX, and HRTEM techniques. The bandgap energy of the Cu-doped ZnO nanoparticle was reduced, enhancing visible-light absorption. The addition of copper ions modified the electronic and optical properties of the photocatalyst, thereby improving its photocatalytic performance. The photocatalytic activity of Cu-doped ZnO nanoparticles was evaluated for the degradation of Direct Red 81 dye (DR-81) as a pollutant in an aqueous solution. Under optimal conditions (DR-81 dye concentration of 20 ppm, Cu-doped ZnO dosage of 0.4 g/100 mL, and 60 minutes of sunlight irradiation), a maximum DR-81 removal efficiency of approximately 70.83% was achieved. A plausible photocatalytic degradation mechanism of DR-81 using Cu-doped ZnO was proposed, revealing that •O₂⁻ and •OH radicals were the primary active species responsible for its degradation. Cyclic experiments demonstrated the high stability and reusability of Cu-doped ZnO, confirming its potential as an economical and environmentally friendly photocatalyst.